2020
DOI: 10.1021/acsphotonics.0c00224
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of Optically Induced Heat Gratings in Metals

Abstract: Diffusion of heat in metals is a fundamental process which, surprisingly, received only a little attention from the research community. Here, we study heat diffusion on the femtosecond and few picoseconds time scales. Specifically, we identify the underlying time scales responsible for the generation and erasure of optically-induced transient Bragg gratings in metal films. We show that due to a interplay between the temporally and spatially nature of the thermo-optic response, heat diffusion affects the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…In bulk metal, both temperatures must be treated as temperature fields varying in space; in these cases, heat diffusion can play a critical role in the dynamics. 8 , 9 In nanoparticles that are sufficiently small compared to the wavelength and focus size of the heating laser, the heating of the particle is uniform. 10 , 11 The temperatures of the electrons and of the lattice can then be taken to be constant across the entire volume of the particle, and they may be treated as scalars.…”
Section: Introductionmentioning
confidence: 99%
“…In bulk metal, both temperatures must be treated as temperature fields varying in space; in these cases, heat diffusion can play a critical role in the dynamics. 8 , 9 In nanoparticles that are sufficiently small compared to the wavelength and focus size of the heating laser, the heating of the particle is uniform. 10 , 11 The temperatures of the electrons and of the lattice can then be taken to be constant across the entire volume of the particle, and they may be treated as scalars.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal effects in these systems were usually ignored, and the optical response was typically interpreted using a temporally-and spatially-local response. In that sense, it would be intriguing to study the thermal response in such systems, to see if (the temporally-and spatially-nonlocal) thermal effects could explain some of the experimental observations, in particular, the strong dependence on the spatial 67,68 and temporal extent of the illumination and on the host properties. [34][35][36] In these cases, changes to the host permittivity may be more important, because of macroscopic transmission changes and thermal lensing effects, which were the main motivation for these studies in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that hot-electron diffusion in thin gold films features a rapid diffusion during the first a few ps and a subsequent 100-fold slower diffusion at longer times by using ultrafast thermomodulation microscopy ( Block et al., 2019 ). It was demonstrated that heat diffusion can be faster than electron-phonon energy transfer rate ( Sivan and Spector, 2020 ). Similar strategies that bypassed the temperature measurement were also explored to quantify these two effects in electrochemistry at plasmonic Au electrode ( Zhan et al., 2019 ; Rodio et al., 2020 ; Yu et al., 2018a , 2018b ; Schorr et al., 2020 ).…”
Section: Thermal and Nonthermal Contributionsmentioning
confidence: 99%